Ways to increase dosing precision of granular foodproducts the batcher of discrete action - Gavva, Oleksandr M.; Kryvoplias-Volodina, Liudmyla; Kokhan, Olena (My University, 2016)
Actual scientific and practical task is to improve the accuracy of dosing bulk solids. Solving this problemwill decrease risks in the production of packaged products. To solve this problem it is necessary to perform the steps: Refine the technology and layout of the modules filling anddosing systems in a packaging machine.
Keywords: flow; construction; dynamic error; потік; конструкція; динамічна похибка; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки